1966
DOI: 10.1161/01.cir.33.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Intercoronary Anastomoses in Congenital Heart Disease

Abstract: Thirty-five cases of congenital heart disease were investigated for the frequency and size of intercoronary anastomoses. Studies of control hearts showed normal intercoronary anastomoses to range to 74 µ in diameter. In those congenital hearts not subjected to surgical procedures, the anastomoses did not differ in size from the control group, even in the presence of anemia, cardiac hypertrophy, and cyanosis. However, the mean age of the cyanotic group was significantly less than the acyanotic group. Even thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…It was unexpected that fetal human hearts contained more native collaterals than the injured neonate and adult mouse as well as diseased adult human hearts, although it is difficult to make comparisons between whole-organ α-SMA staining and angiograms. This finding corresponds with data that suggests collaterals tend to decrease during adolescent years because more were found in the fetal stages compared to neonate humans 57,58 .…”
Section: Discussion__________________________________________________supporting
confidence: 91%
See 1 more Smart Citation
“…It was unexpected that fetal human hearts contained more native collaterals than the injured neonate and adult mouse as well as diseased adult human hearts, although it is difficult to make comparisons between whole-organ α-SMA staining and angiograms. This finding corresponds with data that suggests collaterals tend to decrease during adolescent years because more were found in the fetal stages compared to neonate humans 57,58 .…”
Section: Discussion__________________________________________________supporting
confidence: 91%
“…Using post-mortem perfusions, studies from the 1960s reported the presence of coronary collateral arteries in infants and children 57,58 , but no one has reported whether collaterals develop during embryogenesis. Furthermore, using smooth muscle coverage to identify collateral connections in humans has not been done.…”
Section: Human Fetal and Adult Coronary Collateral Arteriesmentioning
confidence: 99%
“…Similar correlations were not found in normals. This finding is consistent with the concept that coronary sinus oxygen content may be a determinant of coronary blood flow when myo cardial oxygenation mechanisms are altered [Berne, 1957], Enlargement of the coronary arteries has been noted as a response both to hypertrophy and chronic hypoxia in experimental animals [Kerr, 1965], and increased inter-coronary anastomoses have been found in young children with con genital heart disease [Bloor, 1966], Large coronary arteries have been occasionally described in cyanotic congenital heart disease [Bjork, 1966;P erloff, 1968] but there is no evidence that this is a general phenomenon. Changes in coronary bed such as these might make great increases in coronary blood flow possible.…”
Section: Coronary Flow and Myocardial Oxygen Delivery During Stresssupporting
confidence: 89%
“…Directed by the concentration of local messenger substance, endothelial precursor cells sprout out and start forming a dense vascular network with multiple anastomoses. The density of this network is at its peak in neonates and declines subsequently by physiological regression, a process called pruning [14,15,16].…”
Section: Basic Principles Of the Human Coronary Collateral Circulamentioning
confidence: 99%